2015
DOI: 10.1080/10498850.2014.913753
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sensory and Physical Parameters in Chill-Stored Farmed Coho Salmon (Oncorhynchus kisutch)

Abstract: This work focuses on changes in sensory and physical properties of coho salmon (Oncorhynchus kisutch) during chilled storage (24 days). A marked change (p < 0.05) in the results of sensory analysis was found in the flesh of raw chilled fish (fresh odor, elasticity, hardness, oxidized odor) and in the cooked flesh of the chill-stored fish (firmness, neutral flavor, oxidized flavor, oxidized odor) samples. Additionally, physical parameters (gaping, cooking loss) also showed changes (p < 0.05) during chilled stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…[26] In addition, it has been reported [17] 20 demerit points in bogue (B. boops) beneath the fish farm and caught from the natural environment and reported shelf life as 17 and 12 days, respectively. Higher than the shelf life of rainbow trout of this study [39] was found 17 days of shelf life for S. alpinus in ice, 20 days for Atlantic salmon (S. salar) in ice [6] and 17 days for aquacultured coho salmon (O. kisutch) in ice [40] and supported this findings with oxidized odor.…”
Section: Discussionsupporting
confidence: 71%
“…[26] In addition, it has been reported [17] 20 demerit points in bogue (B. boops) beneath the fish farm and caught from the natural environment and reported shelf life as 17 and 12 days, respectively. Higher than the shelf life of rainbow trout of this study [39] was found 17 days of shelf life for S. alpinus in ice, 20 days for Atlantic salmon (S. salar) in ice [6] and 17 days for aquacultured coho salmon (O. kisutch) in ice [40] and supported this findings with oxidized odor.…”
Section: Discussionsupporting
confidence: 71%
“…The cooking loss rate was measured according to the method of RodrãGuez et al (2016). After sample collection, the muscle mass ( w 0 ) was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in golden pompano texture profiles, including hardness and elasticity, determine the marketability of such products (Rodríguez et al, 2016). The structure of the connective tissue in its original state develops into a disordered and loose state during cold storage, with myofibrillar fragmentation and proliferation of specific spoilage bacteria on the surface of the fillet (Li et al, 2013).…”
Section: Change In Texturementioning
confidence: 99%